Stable water isotope data for the AH-1503 ice core drilled at the Allan Hills Blue ice area - Introne, Douglas; Kurbatov, Andrei V.; Mayewski, Paul A.; Yan, Yuzhen (IEDA: US Antarctic Program Data Center, 2018)
Stable water isotope data for the AH-1503 ice core drilled at the Allan Hills Blue ice area have been generated under a collaborative effort by the University of Maine Climate Change Institute (NSF Award#1443263) and Princeton University (NSF Award# 1443263). This data set contains stable isotope data (dD, d18O) of meltwater samples collected from the ice core AH-1503 (76.73243 S, 159.3562 E). Ice core site AH-1503 used the same borehole as AH- BIT58 drilled down to 124 m during the 2011-12 field season. All drilling was conducted with a 3\" Eclipse drill (Ice Drilling Design and Operations (IDDO)).